1996
DOI: 10.1093/nar/24.1.151
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor gene mutations database

Abstract: The current version of the androgen receptor (AR) gene mutations database is described. We have added (if available) data on the androgen binding phenotype of the mutant AR, the clinical phenotype of the affected persons, the family history and whether the pathogenicity of a mutation has been proven. Exonic mutations are now listed in 5'-->3' sequence regardless of type and single base pair changes are presented in codon context. Splice site and intronic mutations are listed separately. The database has allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 44 publications
1
79
1
2
Order By: Relevance
“…In prostate cancer, 17 different single base mutations with amino acid substitutions has been reported. 26 In this study, three silent mutations were detected in three cases, which suggested that AR gene mutation may not play an important role in the disease progression. A previous report showed silent base changes in the AR coding region, but that the significance of AR function was not clear.…”
Section: Discussionmentioning
confidence: 64%
“…In prostate cancer, 17 different single base mutations with amino acid substitutions has been reported. 26 In this study, three silent mutations were detected in three cases, which suggested that AR gene mutation may not play an important role in the disease progression. A previous report showed silent base changes in the AR coding region, but that the significance of AR function was not clear.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast to the androgen receptor gene [43], belonging to the same receptor family, not a single TRβ gene mutation has been reported in non-coding regions or reported to produce abnormal splice variants. Sequencing of cDNA is important in subjects with clinically proven RTH in whom no mutations could be found in genomic DNA.…”
Section: Geneticsmentioning
confidence: 96%
“…13,14 Another important fact is the occurrence of AR gene mutations that can result in a promiscuous receptor with a broad hormone binding and transactivation spectrum. 15,16 Activation of mutated AR has been shown for steroid hormones such as estrogens, progestins, adrenal androgens, and dihydrotestosterone metabolites, and even for the nonsteroidal anti-androgens flutamide and nilutamide. [17][18][19][20][21] Prostate tumor progression can also be accompanied by AR activation through growth factors and protein kinase A activators.…”
mentioning
confidence: 99%